Comparison of Facial Muscle Activation Patterns Between Healthy and Bell’s Palsy Subjects Using High-Density Surface Electromyography - Cui, Han; Zhong, Weizheng; Yang, Zhuoxin; Cao, Xuemei; Dai, Shuangyan; Huang, Xingxian; Hu, Liyu; Lan, Kai; Li, Guanglin; Yu, Haibo (Frontiers in Human Neuroscience, 2021)
Facial muscle activities are essential for the appearance and communication of human beings. Therefore, exploring the activation patterns of facial muscles can be helpful in understanding facial neuromuscular disorders such as Bell’s palsy. Given the irregular shape of the facial muscles as well as their different locations, it should be difficult to detect the activities of whole facial muscles with a few of electrodes. In this study, a high-density surface electromyogram system with 90 electrodes was used to record electromyogram (EMG) signals of facial muscles in both healthy and Bell’s palsy subjects when they did different facial movements. The electrodes were arranged in rectangular arrays covering the forehead and cheek regions of the face. The muscle activation patterns were shown on maps, which were constructed from the root mean square values of all the 90-channel EMG recordings. The experimental results showed that the activation patterns of facial muscles were distinct during doing different facial movements and the activated muscle regions could be clearly observed. Moreover, two features of the activation patterns, 2D correlation coefficient (corr2) and Centre of Gravity (CG), were extracted to quantify the spatial symmetry and the location of activated muscle regions respectively. Furthermore, the deviation of activated muscle regions on the paralyzed side of a face compared to the healthy side was quantified by calculating the distance between two sides of CGs. The results revealed that corr2 of the activated facial muscle region (classified into forehead region and cheek region) in Bell’s palsy subjects was significantly (P<0.05) lower than that in healthy subjects, while CG distance of activated facial region in Bell’s palsy subjects was significantly(P<0.05) higher than that in healthy subjects. The correlation between corr2 of these region and Bell’s palsy (assessed by the Facial Nerve Grading Scale 2.0) was also significant (P<0.05) in Bell’s palsy subjects. The spatial information on activated muscle regions may be useful in the diagnosis and treatment of Bell’s palsy in the future.